2016
DOI: 10.1016/j.addbeh.2016.01.010
|View full text |Cite
|
Sign up to set email alerts
|

Gambling transitions among adult gamblers: A multi-state model using a Markovian approach applied to the JEU cohort

Abstract: The status of problem gambler is unstable over time, whereas we found stability among non-problem gamblers. Our findings suggest the existence of vulnerability and protective factors in gambling. These results lead to think about preventive actions and adaptive care, such as cognitive-behavioral therapy or researching gambling problems in people with an anxiety disorder or ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 29 publications
0
24
0
3
Order By: Relevance
“…Links between social gambling and GD are not linear and different factors-individual and environmental factors or behavioral characteristics linked to gamblingmay influence gambling status and the development of the gambling behavior 1) . Problem gambling (PG) is more likely to occur among men [1][2][3]8) , with psychiatric disorders 8) , or individuals of extreme age [9][10][11][12] . Environmental factors, such as level of income, socio-economic integration, or social support and working status have an influence, both on PG prevalence worldwide and on an individual's gambling trajectory between social gambling and GD 1,4,8) .…”
Section: Introductionmentioning
confidence: 99%
“…Links between social gambling and GD are not linear and different factors-individual and environmental factors or behavioral characteristics linked to gamblingmay influence gambling status and the development of the gambling behavior 1) . Problem gambling (PG) is more likely to occur among men [1][2][3]8) , with psychiatric disorders 8) , or individuals of extreme age [9][10][11][12] . Environmental factors, such as level of income, socio-economic integration, or social support and working status have an influence, both on PG prevalence worldwide and on an individual's gambling trajectory between social gambling and GD 1,4,8) .…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden, people born outside the country also have elevated risk ( Abbott et al, 2014 ). In addition to some gambling and sociodemographic factors, there are strong associations with personality characteristics including impulsivity, mental health disorders and substance use and misuse ( Bruneau et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…It can be assumed that giving up gambling completely under medical supervision for at least 1 month could help reinforce feelings of self-efficacy and reduce cognitive distortions, with a decrease in the severity of the disorder as a potential corollary. Indeed, in a previous analysis, we observed that giving up gambling for a period of at least 1 month was associated with a lower risk of changing status from non-problem gambler to problem gambler (Bruneau et al., 2016). …”
Section: Discussionmentioning
confidence: 87%